Use of social networks as a CSR communication tool - Francisco-Javier Cortado (Taylor & Francis Group, 2016)
The aim of this paper is to analyse the use of online social networks as a tool for Corporate Social Responsibility (CSR) communication and management. To this end, an analysis was performed of the messages posted by the 20 Spanish companies with the highest market capitalisation and the responses that they received on two of the most popular online social networks, Facebook and Twitter. The results of the analysis of these data show that the tendency has been to use social networks for the one-way communication of aspects of CSR related with the organisation. Therefore, it is necessary to change the way companies communicate their CSR issues by shifting to a two-way communication approach, as has been the case in other kinds of enterprise relations with their stakeholders.